Gender and motor competence affects perceived likelihood and importance of physical activity outcomes among 14 year olds. (20th October 2015) - Hands, B.; Parker, H. E.; Rose, E.; Larkin, D.
Abstract: Background: Perceptions of the effects of physical activity could facilitate or deter future participation. This study explored the differences between gender and motor competence at 14 years of age in the perceptions of likelihood and importance of physical activity outcomes. Method: The sample comprised 1582 14‐year‐old adolescents (769 girls) from the Western Australian Pregnancy Cohort (Raine) Study. Four motor competence groups were formed from a standardized Neuromuscular Developmental Index score (McCarron 1997). Perceptions of the likelihood and the importance of 15 physical activity outcomes were measured by a questionnaire developed for the NSW Schools Fitness and Physical Activity Survey (Booth et al . 1997). Gender (two) × motor competence (four) analyses of variance and Tukey post hoc were conducted on outcome scores ( P  < 0.02) using SPSS version 17. Results: Gender differences were found in the perceived likelihood and importance of physical activity outcomes within competition, social friendships and injury domains. Motor competence was significant in the perceived likelihood of physical health ( P  < 0.001), psychosocial ( P  < 0.009) and competition ( P  < 0.002) outcomes, with lower perceptions by the least competent groups. Significantly lower importance was perceived for academic outcomes for 14 year olds categorized with low compared with high motor competence ( P  < 0.005). Regardless of motor competence and gender, the same health and fun outcomes were ranked the highest in likelihood and the highest in importance. Conclusion: Although level of motor competence at 14 years affected the perceived likelihood of health, social and fun outcomes from future participation in physical activity, adolescents highly valued these outcomes, whereas gender affected competition and winning, outcomes that were less valued. Physical activity that promotes these key and valued outcomes may encourage young people's ongoing involvement in physical activity, especially for those at risk of low participation.